An activity theoretical model for social interaction in computer games - Ang, Chee Siang; Zaphiris, Panayiotis; Wilson, Stephanie (My University, 2011)
Computer games have for years been the focus of Human Computer Interaction (HCI)-oriented research. For example, researchers have looked at playability and have developed heuristics for evaluating fun as well as usability of computer games (Desurvire, et al. 2004; Fabricatore, et al. 2002; Federoff 2002). Although much of this research has revolved around enhancing engagement by improving player-game interaction, some (Ducheneaut, et al. 204; Ducheneaut, et al. 2006; Kolo and Baur 2004) have begun to look into the social aspects of gaming as most computer game play is social. Surveys have shown that almost 60 percent of game players play with friends; 33 percent play with siblings and 25 percent play with spouses or parents (Jenkins 2006). Similarly, within the area of game-based learning, the focus is moving from treating games as a standalone tool that delivers knowledge to learners in an enjoyable way, to utilising games as a medium for social interaction and collaboration.